The Mediating Effect of Supplier Relationship Management on CSR and Marketing Performance Relationship - Kwamena Minta Nyarku; Stephen Oduro (Universitas Pasundan, 2019)
The study sought to examine the mediating outcome of supplier relationship management (SRM) on the CSR and marketing performance (MP) relationship. The study was descriptive, quantitative in nature with a questionnaire as its main data collection instrument. A purposive sampling approach was employed to select 317 owners/managers of the manufacturing firms. Data collected was analyzed using Structural Equation Model–Partial Least Square statistical software. The study proposed two models; model 1 without mediation effect and model 2 with mediation effect. The results revealed a direct significant positive relationship between CSR and MP and CSR and SRM; including a direct positive relationship between SRM and MP. However, the direct link between CSR and MP was not supported, when the mediating variable was included; but shows that SRM fully mediates the CSR and MP tie. The effect of SRM explains the effect of CSR on MP. Appearing to be the first study to examine the mediation role of supplier relationship management, this study discovered the novel path through which CSR is linked to a company’s marketing performance, as well as key CSR engagements that can enhance supplier relationship management and marketing performance.